Hybrid mechanisms for robust synchronization and coordination of multi-agent networked sampled-data systems. (January 2019) - Poveda, Jorge I.; Teel, Andrew R.
Abstract: We present a novel approach for the design of robust feedback coordination and control mechanisms for networks of asynchronous nonlinear multi-agent systems (MAS). Each agent corresponds to a sampled-data system characterized by a continuous-time plant, a discrete-time controller with logic or integer states, and a sampler/zero-order hold with a local clock. The goal is to robustly stabilize an application-dependent compact set defined a priori for the MAS, taking into account the asynchronous nature of the triggering mechanisms of the agents, and the limited information in the network. To solve this problem, we propose an emulation-like approach, where the feedback mechanism for each agent is initially designed for a nominal ideal synchronous MAS with a single logic state. Unlike existing emulation results for networked sampled-data systems with a single triggering mechanism, the implementation of multiple triggering mechanisms in MAS requires additional decentralized coordination algorithms to guarantee that the implemented system robustly emulates the behavior of the nominal synchronous system. Therefore, we propose a decentralized synchronization and coordination mechanism that controls the triggering mechanisms of the agents, guaranteeing robust stabilization of the closed-loop MAS. Our results are established by using Lyapunov tools, the invariance principle, and robustness corollaries for set-valued hybrid dynamical systems.